Investigation of complexation and antimicrobial activity of gramicidin S in the presence of lipopeptides from Bacillus subtilis - Vlok, Nicolaas Mare (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.